WAYS TO IMPROVE THE USE OF MARKETING COMMUNICATIONS IN TOURISM - Mamatkulova Shoira Jalolovna (Web of Journals Publishing, 2023)
This article provides recommendations on ways to improve the use of marketing communications tools in tourism.
Keywords: marketing, tourism, communication, advertising, exhibitions and fairs, personal selling.